Magnetic slurry as well as preparation method and application thereof

Through the mixing of multiple alloy powders of soft magnetic alloy powder and the use of thermosetting resins, the problem of insufficient strength and stability of magnetic slurry in high-temperature environments is solved, and the high strength and high temperature resistance of inductors are improved.

CN120236842APending Publication Date: 2025-07-01HENGDIAN GRP DMEGC MAGNETICS CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202311849109.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-12-29
Publication Date
2025-07-01

AI Technical Summary

Technical Problem

The existing magnetic slurries have insufficient performance stability and strength in high-temperature environments, making it difficult to meet the needs of miniaturized and multifunctional inductors.

Method used

A variety of alloy powders are used to mix soft magnetic alloy powders, combining thermosetting and thermoplastic resin binders, and enhance the strength of the inductor and high temperature resistance by improving the bulk density and flexibility.

Benefits of technology

It improves the strength and high temperature resistance of the inductor, and achieves the high intensity characteristics of the inductor and excellent high temperature stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004640533930000061
    Figure BDA0004640533930000061
  • Figure BDA0004640533930000091
    Figure BDA0004640533930000091
  • Figure BDA0004640533930000131
    Figure BDA0004640533930000131
Patent Text Reader

Abstract

The invention provides magnetic slurry as well as a preparation method and application thereof. The magnetic slurry comprises soft magnetic alloy powder, a binder and an auxiliary agent; the soft magnetic alloy powder comprises a first alloy, a second alloy and a third alloy; the binder comprises a mixture of thermosetting resin and thermoplastic resin; the auxiliary agent comprises a solvent. By adopting the magnetic slurry disclosed by the invention, the strength and the high-temperature resistance of the inductor can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of magnetic materials, and relates to a magnetic slurry, a preparation method thereof and an application thereof. Background Art

[0002] With the development of electronic power technology, it is an inevitable trend for power inductors to develop towards miniaturization, multi-functionality and integration. Especially in various applications such as home appliances, industrial equipment, vehicles, etc., there are higher requirements for the strength of inductors and the performance stability at high temperatures.

[0003] CN113948262A discloses a preparation method of a magnetic slurry, a common mode inductor and a common mode inductor cover plate. The magnetic slurry in this patent is a mixture of magnetic powder, PVB binder and solvent. The magnetic powder is a mixture composed of one or more of alloy-based FeNi, FeSiCr, and FeSiAl, and the magnetic powder has magnetic anisotropy. Since the PVB binder is used in the magnetic slurry, the performance stability of the prepared inductor in a high-temperature environment and the strength of the inductor are both limited to a certain extent.

[0004] CN106887290A discloses a magnetic slurry, a preparation method thereof and a preparation method of a magnetic sheet. The magnetic slurry in this patent includes magnetic powder and an organic carrier. The mass ratio of the magnetic powder to the organic carrier is 1:0.7 to 1:0.9; the organic carrier includes, by mass percentage: 8-10% of a binder, 82-90% of a solvent, 0.1-1% of an antifoaming agent, 0.1-1% of a dispersant and 1-6% of a plasticizer. The binder is polyvinyl butyral, and the solvent includes an alcohol solvent and an ester solvent. The magnetic sheet prepared from the magnetic slurry of this patent is not easy to crack during tape casting molding, has good flatness of the magnetic sheet and a relatively high Q value. However, the resin selected for the magnetic slurry in this patent makes the magnetic sheet have relatively poor high-temperature resistance and strength.

[0005] CN103426585A discloses a slurry for NFC magnetic sheets. The slurry for NFC magnetic sheets contains magnetic powder, binder, curing agent, dispersant and solvent; the magnetic powder is flat Fe-Si-Al-Mo-Cu soft magnetic powder, and the mass ratio of Fe, Si, Al, Mo to copper is (85-9x):9.6:5.4:4x:5x, and 1≤x≤1.5; the dispersant is vinyl bis stearamide. By using vinyl bis stearic acid amide as the dispersant in the slurry for NFC magnetic sheets, the uniform distribution of magnetic powder in the slurry is achieved, but it cannot meet the requirement of maintaining excellent stability of the magnetic sheet at high temperatures.

[0006] CN101494110A discloses a manufacturing method of a cast slurry type inductance element. The magnetic slurry in this patent uses magnetic powder including iron, silicon, cobalt, nickel, aluminum, platinum, nickel zinc, manganese zinc, permalloy, high-flux powder, iron-silicon-aluminum alloy and its oxides as the main body, and epoxy resin or polyester resin binder as the auxiliary material. The mass ratio of the main powder is 50% - 96%, and the ratio of the auxiliary material is 4% - 50%. The main material and the auxiliary material are stirred evenly, and then poured into a mold containing a coil to be cured and demolded to obtain an inductor. This patent cannot guarantee obtaining an inductor with high strength.

[0007] Therefore, there is an urgent need to provide a solution that can improve the strength and high-temperature resistance of the inductor at the same time. Summary of the Invention

[0008] Aiming at the deficiencies of the prior art, the purpose of the present invention is to provide a magnetic slurry, its preparation method and application. The magnetic slurry of the present invention includes soft magnetic alloy powder, binder and additive. Among them, with the synergistic cooperation of the first alloy, the second alloy and the third alloy in the soft magnetic alloy powder, alloy powders of different types and different particle sizes can be mixed, so as to improve the packing density of the soft magnetic alloy powder, and further improve the strength of the magnetic sheet formed by casting the magnetic slurry, and improve the strength of the inductor; moreover, by selecting a mixture of thermoplastic resin and thermosetting resin as the binder, the strength after curing of the inductor can be further improved to achieve the high-strength characteristic of the inductor, and the high-temperature resistance of the inductor can be effectively improved.

[0009] To achieve this purpose, the present invention adopts the following technical solutions:

[0010] In the first aspect, the present invention provides a magnetic slurry, which includes soft magnetic alloy powder, binder and additive;

[0011] The soft magnetic alloy powder includes a first alloy, a second alloy and a third alloy;

[0012] The binder includes a mixture of thermosetting resin and thermoplastic resin;

[0013] The additive includes a solvent.

[0014] The present invention provides a magnetic paste, which comprises soft magnetic alloy powder, binder and additives. Among them, with the synergistic cooperation of the first alloy, the second alloy and the third alloy in the soft magnetic alloy powder, alloy powders of different types and different particle sizes can be mixed, so as to improve the packing density of the soft magnetic alloy powder, and further improve the strength of the magnetic sheet formed by casting the magnetic paste and the strength of the inductor. Moreover, the binder adopts a mixture of thermosetting resin and thermoplastic resin. The thermoplastic resin can endow the magnetic sheet with a certain degree of flexibility during the uncured process of the magnetic sheet, which is convenient for winding the magnetic sheet, while the thermosetting resin can effectively improve the high-temperature resistance of the inductor and provide relatively high mechanical strength and impact strength after curing. Therefore, choosing a mixture of thermoplastic resin and thermosetting resin as the binder can further improve the strength of the inductor after curing, so as to realize the high-strength characteristics of the inductor and effectively improve the high-temperature resistance of the inductor.

[0015] Preferably, based on the total mass of the soft magnetic alloy powder being 100%, the mass fraction of the first alloy is 15-25%, for example, it can be 15%, 18%, 20%, 22%, 23% or 25%, etc.

[0016] Preferably, based on the total mass of the soft magnetic alloy powder being 100%, the mass fraction of the second alloy is 20-40%, for example, it can be 20%, 22%, 25%, 28%, 30%, 32%, 35%, 38% or 40%, etc.

[0017] Preferably, based on the total mass of the soft magnetic alloy powder being 100%, the mass fraction of the third alloy is 35-65%, for example, it can be 35%, 40%, 45%, 50%, 55%, 60% or 65%, etc.

[0018] Preferably, the average Wadell sphericity of the first alloy is 70-100%, for example, it can be 70%, 75%, 80%, 85%, 90%, 95% or 100%, etc., and preferably 80-100%.

[0019] In the present invention, the sphericity of the alloy will affect the packing density of the soft magnetic alloy powder. If the sphericity is relatively poor, the packing density will decrease. The same applies to the other alloys.

[0020] Preferably, the D50 particle size of the first alloy is 30-50μm, for example, it can be 30μm, 35μm, 40μm, 45μm or 50μm, etc., and preferably 35-45μm.

[0021] Preferably, the first alloy comprises FeNi alloy and / or FeNiMo alloy, and preferably FeNi alloy.

[0022] Preferably, the average Wardell sphericity of the second alloy is 85-100%, for example, it can be 85%, 88%, 90%, 95%, 98% or 100%, etc., and preferably 90-100%.

[0023] Preferably, the particle size D50 of the second alloy is 25-45 μm, for example, it can be 25 μm, 30 μm, 35 μm, 40 μm or 45 μm, etc., and preferably 30-40 μm.

[0024] Preferably, the second alloy includes any one or a combination of at least two of FeSi alloy, FeSiAl alloy or FeSiCr alloy, and preferably FeSi alloy.

[0025] Preferably, the average Wardell sphericity of the third alloy is 85-100%, for example, it can be 85%, 88%, 90%, 95%, 98% or 100%, etc., and preferably 90-100%.

[0026] Preferably, the particle size D50 of the third alloy is 5-12 μm, for example, it can be 5 μm, 7 μm, 9 μm, 10 μm or 12 μm, etc., and preferably 7-10 μm.

[0027] In the present invention, the particle size of the third alloy is relatively small, which can effectively fill the voids between the first alloy and the second alloy, increase its packing density, and further enable the cured and formed inductance magnet to have high strength characteristics.

[0028] Preferably, the third alloy includes carbonyl iron powder and / or reduced iron powder, and preferably carbonyl iron powder.

[0029] Preferably, the thermosetting resin includes boron-modified phenolic resin and / or molybdenum-modified phenolic resin; the number average molecular weight of the thermosetting resin is 1000-5000, for example, it can be 1000, 2000, 3000, 4000 or 5000, etc.

[0030] In the present invention, the boron-modified phenolic resin replaces the C-C chemical bond with a B-O chemical bond, and the molybdenum-modified phenolic resin replaces the C-C chemical bond with a Mo-O chemical bond. The thermosetting resin used in the present invention connects the benzene rings with B-O bonds or Mo-O bonds instead of C-C bonds of traditional phenolic resins, and its bond energy is increased, so that the heat resistance of the three-dimensional cross-linked network structure in the cured product is enhanced.

[0031] Preferably, the thermoplastic resin includes a first thermoplastic resin and / or a second thermoplastic resin.

[0032] Preferably, the first thermoplastic resin includes a polyamide resin and / or a polysulfone resin; the number average molecular weight of the first thermoplastic resin is 100,000 - 250,000, and can be, for example, 100,000, 150,000, 200,000, or 250,000, etc.

[0033] In the present invention, after blending the first thermoplastic resin and the phenolic resin, co-curing can occur between them during the curing process or a partially interpenetrating network structure can be formed, so as to improve the mechanical strength and impact strength of the final product.

[0034] Preferably, the second thermoplastic resin includes a polyurethane resin; the number average molecular weight of the second thermoplastic resin is 50,000 - 150,000, and can be, for example, 50,000, 80,000, 100,000, 120,000, or 150,000, etc.

[0035] In the present invention, after blending the second thermoplastic resin and the phenolic resin, the flexible chains of the polyurethane resin can absorb the energy acting on the phenolic resin in a timely manner during the semi-curing process, making the magnetic sheet more flexible after calendaring, and thus facilitating the winding and hot pressing forming of the magnetic sheet.

[0036] Preferably, the mass ratio of the thermosetting resin to the thermoplastic resin is (2 - 4):1, and can be, for example, 2:1, 2.5:1, 3:1, 3.5:1, or 4:1, etc.

[0037] Preferably, the mass ratio of the first thermoplastic resin to the second thermoplastic resin is (1 - 3):1, and can be, for example, 1:1, 1.5:1, 2:1, 2.5:1, or 3:1, etc.

[0038] In the present invention, if the mass ratio of the first thermoplastic resin to the second thermoplastic resin is too high, it will cause the magnetic sheet to have a large rigidity, the bonding degree between the magnetic sheets will decrease, and further the inductance value, strength, and temperature resistance performance of the inductor will all deteriorate; if the mass ratio of the first thermoplastic resin to the second thermoplastic resin is too low, the proportion of the co-curing or the formation of a partially interpenetrating network structure between the first thermoplastic resin and the phenolic resin in the cured magnet will decrease, resulting in a decrease in the strength of the magnet.

[0039] Preferably, the solvent includes a combination of at least two of acetone, methyl ethyl ketone, ethanol, propanol, ethyl acetate, or butyl acetate. Typical but non-limiting combinations include the combination of ethyl acetate and methyl ethyl ketone, the combination of acetone and butyl acetate, and the combination of acetone and propanol.

[0040] Preferably, the auxiliary agent further includes a dispersant and a coupling agent.

[0041] In the present invention, a dispersant and a coupling agent are selected as additives, which can make the soft magnetic alloy powder and the binder combine more closely to meet the requirements of strength and high temperature resistance, and help the magnetic slurry for casting.

[0042] Preferably, the dispersant includes any one or a combination of at least two of BYK-185, AKM-0531 or SRE-42413, and is preferably AKM-0531.

[0043] Preferably, the coupling agent includes a mixture of a silane coupling agent and a titanate coupling agent; the mass ratio of the silane coupling agent to the titanate coupling agent is 5:(1-3), and can be, for example, 5:1, 5:2 or 5:3, etc.

[0044] Preferably, the magnetic slurry, by weight, comprises the following components:

[0045]

[0046] Among them, the amount of the dispersant can be, for example, 0.1 part, 0.2 part, 0.5 part, 1 part or 1.5 parts, etc. The amount of the binder can be, for example, 2 parts, 3 parts, 4 parts, 5 parts or 6 parts, etc. The amount of the coupling agent can be, for example, 0.5 part, 0.8 part, 1 part, 1.5 parts or 2 parts, etc. The amount of the solvent can be, for example, 20 parts, 30 parts, 35 parts, 40 parts, 45 parts or 50 parts, etc.

[0047] In the present invention, if the amount of the binder is too large, the inductance value and high temperature stability of the inductor will decrease; if the amount of the binder is too small, the proportion of the magnetic substance will increase, resulting in an increase in the inductance value and deviation from the required range of the target inductance value. On the other hand, if the amount of the binder in the magnetic sheet is small, the strength of the magnetic sheet will decrease and the bonding degree of the magnets during the inductor pressing process will decrease, deteriorating the strength performance of the inductor.

[0048] In a second aspect, the present invention provides a method for preparing the magnetic slurry according to the first aspect, the preparation method comprising:

[0049] (1) Mixing a first alloy, a second alloy and a third alloy to obtain soft magnetic alloy powder;

[0050] (2) Mixing the soft magnetic alloy powder and a solvent to obtain the magnetic slurry.

[0051] As a preferred technical solution of the present invention, the preparation method specifically comprises the following steps:

[0052] (Ⅰ) Mixing a first alloy, a second alloy and a third alloy to obtain soft magnetic alloy powder;

[0053] (II) Mix the dispersant with part of the solvent, then add the soft magnetic alloy powder, and ball mill at a rotation speed of 200 - 300 rpm (for example, it can be 200 rpm, 250 rpm, or 300 rpm, etc.) for 4 - 6 h (for example, it can be 4 h, 5 h, or 6 h, etc.). After drying, a mixed alloy powder with surface treatment by the dispersant is obtained;

[0054] (III) Mix the coupling agent with part of the solvent, then add the mixed alloy powder with surface treatment by the dispersant for mixing. After drying, a mixed alloy powder with surface treatment by the coupling agent is obtained;

[0055] (IV) Ball mill the mixed alloy powder with surface treatment by the coupling agent, the binder, and the remaining solvent. The rotation speed of the ball milling is 150 - 300 rpm (for example, it can be 150 rpm, 200 rpm, 250 rpm, 200 rpm, or 300 rpm, etc.), and the ball milling time is 18 - 24 h (for example, it can be 18 h, 20 h, 22 h, or 24 h, etc.). Then, it is sieved through a 50 - 100 mesh (for example, it can be 50 mesh, 80 mesh, or 100 mesh, etc.) and vacuum stirred and degassed for 10 - 15 min (for example, it can be 10 min, 12 min, or 15 min, etc.) to obtain the magnetic slurry.

[0056] In the third aspect, the present invention provides a magnetic sheet, and the magnetic sheet is obtained by casting the magnetic slurry described in the first aspect.

[0057] Preferably, the preparation method of the magnetic sheet includes: pouring the magnetic slurry into a trough, and keeping stirring. Adjust the gap of the casting machine blade according to the situation of the slurry, control the casting speed, and make the magnetic slurry into a magnetic sheet.

[0058] In the fourth aspect, the present invention provides an inductor, and the inductor includes the magnetic sheet described in the third aspect.

[0059] Preferably, the preparation method of the inductor includes:

[0060] (a) Cut the magnetic sheet into a fixed size, place the base magnetic sheet and the intermediate magnetic sheet from bottom to top in sequence, and embed the hollow coils fixed in an array at intervals on the thermosensitive adhesive into the intermediate magnetic sheet. Then, keep it at a temperature of 80 - 135 °C for 20 - 60 s, press it with a pressure of 20 - 40 MPa, and then press the cover magnetic sheet on the topmost layer to form an inductor assembly; the pressure for pressing the cover magnetic sheet is 90 - 180 MPa, the pressing temperature is 70 - 150 °C, and the pressure holding time is 30 - 60 s;

[0061] (b) Cut the inductor assembly to obtain inductor units; grind the two ends of the inductor units to a set size so that the copper wire ends at both ends of the hollow coil are exposed, and then successively go through curing, roller spraying, laser paint stripping, electroplating and testing to obtain inductors; wherein, the curing process adopts step-by-step curing, and the curing process is to cure at 150°C for 1-2h first, and then cure at 180°C for 2-3h.

[0062] In step (a), the temperature is 80-135°C, for example, it can be 80°C, 90°C, 100°C, 110°C, 120°C, 130°C or 135°C, etc.; the pressure is 20-40MPa, for example, it can be 20MPa, 30MPa, 35MPa or 40MPa, etc.; the pressure is 90-180MPa, for example, it can be 90MPa, 100MPa, 120MPa, 140MPa, 160MPa or 180MPa, etc.; the lamination temperature is 70-150°C, for example, it can be 70°C, 80°C, 100°C, 120°C, 130°C or 150°C, etc.

[0063] In the present invention, after the magnetic slurry is cast to form a base magnetic sheet, an intermediate magnetic sheet and a covering magnetic sheet respectively, several arranged hollow coils are embedded into the intermediate magnetic sheet at one time, so that mass production of power inductors can be realized at one time.

[0064] The numerical ranges described in the present invention not only include the above-listed point values, but also include any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention does not exhaustively list the specific point values included in the ranges.

[0065] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0066] The present invention provides a magnetic slurry, which includes soft magnetic alloy powder, binder and additives. Among them, with the synergistic cooperation of the first alloy, the second alloy and the third alloy in the soft magnetic alloy powder, alloy powders of different types and different particle sizes can be mixed, so as to improve the packing density of the soft magnetic alloy powder, and further improve the strength of the magnetic sheet formed by casting the magnetic slurry and the strength of the inductor; and, the binder adopts a mixture of thermosetting resin and thermoplastic resin. The thermoplastic resin can endow the magnetic sheet with a certain degree of flexibility during the uncured process of the magnetic sheet, which is convenient for winding the magnetic sheet, while the thermosetting resin can effectively improve the high-temperature resistance of the inductor and provide higher mechanical strength and impact strength after curing. Therefore, choosing a mixture of thermoplastic resin and thermosetting resin as the binder can further improve the strength of the inductor after curing to achieve the high-strength characteristics of the inductor and effectively improve the high-temperature resistance of the inductor. Detailed Embodiment

[0067] The technical solution of the present invention is further illustrated below through specific implementation methods.

[0068] Example 1

[0069] This embodiment provides a magnetic slurry, which includes the following components in parts by weight:

[0070]

[0071] The soft magnetic alloy powder is composed of a first alloy, a second alloy and a third alloy. The first alloy is a FeNi alloy powder with an average Wardell sphericity of 88% and a D50 of 41.8 μm. The second alloy is a FeSi alloy powder with an average Wardell sphericity of 92.5% and a D50 of 35.1 μm. The third alloy is a carbonyl iron powder with an average Wardell sphericity of 94.4% and a D50 of 8.2 μm. The mass ratio of the first alloy, the second alloy and the third alloy is 2:3:5.

[0072] The thermosetting resin in the binder is a boron-modified phenolic resin in which BO chemical bonds replace CC chemical bonds; the thermoplastic resin is a mixture of polyamide resin and polyurethane resin, wherein the mass ratio of the thermosetting resin to the thermoplastic resin is 3:1, and the mass ratio of the polyamide resin to the polyurethane resin in the thermoplastic resin is 2:1; the dispersant is AKM-0531; the coupling agent is a mixture of a silane coupling agent and a titanate coupling agent, and the mass ratio of the two is 5:3; the solvent is a combination of ethyl acetate and butanone, and the mass ratio of the two is 2:1.

[0073] This embodiment also provides a method for preparing the magnetic slurry, comprising the following steps:

[0074] (1) mixing the first alloy, the second alloy and the third alloy to obtain soft magnetic alloy powder;

[0075] (2) Mixing the dispersant AKM-0531 with part of the solvent, and then adding the soft magnetic alloy powder and the ball milling medium zirconium oxide balls, and ball milling and mixing at a speed of 300 rpm for 4 hours in a ball mill to obtain a suspension, and then drying the solvent to obtain a mixed alloy powder with the dispersant surface treated;

[0076] (3) The coupling agent and part of the solvent are mixed evenly to prepare a coupling agent solution with a concentration of 20%, and then the mixed powder is added to the coupling agent solution and mixed evenly, and then dried to obtain a mixed alloy powder with a coupling agent surface treatment for later use;

[0077] (4) adding the mixed alloy powder treated in step (3), the binder, and the remaining solvent to the ball milling medium zirconium oxide balls for ball milling at a ball milling rate of 200 rpm for 20 h;

[0078] (5) The slurry obtained after ball milling in step (4) is sieved through a 50-mesh sieve, and then vacuum stirred and defoamed for 15 min to obtain a magnetic slurry.

[0079] Example 2

[0080] The difference between this example and Example 1 is only that the mass ratio of the first alloy, the second alloy, and the third alloy is 5:2:3.

[0081] Example 3

[0082] The difference between this example and Example 1 is only that the weight part of the binder is adjusted to 6 parts.

[0083] Example 4

[0084] The difference between this example and Example 1 is only that the weight part of the binder is adjusted to 2 parts.

[0085] Example 5

[0086] The difference between this example and Example 1 is only that the ratio of the thermosetting resin to the thermoplastic resin in the binder is 4:1.

[0087] Example 6

[0088] The difference between this example and Example 1 is only that the mass ratio of the polyamide resin to the polyurethane resin in the thermoplastic resin is 3:1.

[0089] Example 7

[0090] The difference between this example and Example 1 is only that the weight part of the added coupling agent is adjusted to 2 parts.

[0091] Example 8

[0092] The difference between this example and Example 1 is only that the first alloy is FeNi alloy powder with an average Wardell sphericity of 52.9%, and its D50 is 40.4 μm; the second alloy is FeSi alloy powder with an average Wardell sphericity of 64.5%, and its D50 is 33.7 μm; the third alloy is carbonyl iron powder with an average Wardell sphericity of 81.3%, and its D50 is 7.7 μm; the mass ratio of the first alloy, the second alloy, and the third alloy is 2:3:5.

[0093] Example 9

[0094] The difference between this example and Example 1 is only that the weight part of the binder is adjusted to 15 parts.

[0095] Example 10

[0096] The difference between this example and Example 1 is only that no coupling agent is added.

[0097] Example 11

[0098] The difference between this example and Example 1 is only that only polyamide resin is included in the thermoplastic resin.

[0099] Example 12

[0100] The difference between this example and Example 1 is only that the weight parts of the binder are adjusted to 1 part.

[0101] Example 13

[0102] The difference between this example and Example 1 is only that the mass ratio of polyamide resin to polyurethane resin in the thermoplastic resin is adjusted to 4:1.

[0103] Example 14

[0104] The difference between this example and Example 1 is only that the mass ratio of polyamide resin to polyurethane resin in the thermoplastic resin is adjusted to 0.5:1.

[0105] Comparative Example 1

[0106] The difference between this comparative example and Example 1 is only that the soft magnetic alloy powder is composed of a first alloy and a second alloy, and the mass ratio of the first alloy to the second alloy is 4:6.

[0107] Comparative Example 2

[0108] The difference between this comparative example and Example 1 is only that only thermoplastic resin is used as the binder.

[0109] Performance Test

[0110] Pour the magnetic slurries provided in the above examples and comparative examples into the material tank, and keep stirring. Adjust the gap of the doctor blade of the casting machine according to the situation of the slurry, control the casting speed, and make the slurry into a green magnetic sheet with a thickness of 0.4 ± 0.02 mm;

[0111] Cut the green magnetic sheet into a fixed size, place the base magnetic sheet and the intermediate magnetic sheet in sequence from bottom to top, and embed the hollow coils arranged at array intervals and fixed on the thermosetting adhesive into the intermediate magnetic sheet. Keep it warm at 105 °C for 40 s, press it with a pressure of 25 MPa, and then press the cover magnetic sheet on the topmost layer to form an inductance assembly; the pressure for pressing the cover magnetic sheet is 100 MPa, the pressing temperature is 90 °C, and the pressure holding time is 50 s; both ends of the used hollow coil have leads, the coil is wound with an enameled wire with a self-adhesive layer, the enameled wire is a square wire, the wire thickness is 0.07 mm, the wire width is 0.23 mm, and it is wound for 2 layers with a total of 6.5 turns; the inside of the hollow coil is in the shape of an elliptical track;

[0112] Cut the inductor assembly to obtain inductor units; grind the two ends of the inductor units to a set size so that the copper wire ends at both ends of the hollow coil are exposed, and then go through curing, rolling spraying, laser paint stripping, electroplating and testing in sequence to obtain the inductor. The curing process adopts step-by-step curing, and the curing process is to cure at 150 °C for 1 h first, and then cure at 180 °C for 2 h.

[0113] (1) Inductor performance test:

[0114] Use a WK6500B impedance analyzer to test the inductance value, saturation current and DC resistance of the inductor sample, and the test conditions are 1 MHz & 1 V.

[0115] (2) Inductor strength test:

[0116] Use a JSV-500D strength tester to test the strength of the inductor and record the magnitude of the force when the inductor breaks.

[0117] (3) Inductor high-temperature resistance performance test:

[0118] Use the national standard GB-T2423.2-2008 to evaluate the attenuation degree of the inductor after high-temperature cycling. First record the inductance value of the untreated inductor, then process the inductor at 165 °C / 250 h, and then test its inductance value. Compare the inductance values before and after processing and calculate its attenuation degree.

[0119] The test results of each example and comparative example are shown in Table 1.

[0120] Table 1

[0121]

[0122]

[0123] Analysis:

[0124] As can be seen from Table 1, by using the magnetic slurries of Examples 1-7 of the present invention, the inductance value of the prepared inductor meets 680 nH ± 15%, the strength > 280 N, and the attenuation degree of the inductance value is less than 1.8% after high-temperature treatment at 165 °C / 250 h. It fully proves that the inductor prepared by the present invention has high strength and excellent high-temperature stability.

[0125] Compared with Example 1, in Example 8, alloy powder with relatively poor sphericity was selected in the selection of soft magnetic alloy powder, which would also lead to a decrease in the packing density of the magnet, resulting in a decrease in the inductance value and strength.

[0126] In Example 9, compared with Example 1, an excessive amount of binder was added, resulting in too much non-magnetic material in the inductor, which led to a decrease in magnetic permeability and thus affected the inductance value. Although the strength of its inductance increased to some extent, the excessive resin was significantly affected in a high-temperature environment. In Example 12, compared with Example 1, too little binder was added, which led to too large a proportion of magnetic material in the inductor magnet, causing the inductance value to deviate from the target requirement (680 nH ± 15%). At the same time, due to too little content of the binder, the strength of the magnet decreased significantly.

[0127] In Example 10, compared with Example 1, a coupling agent was not added in the selection of related additives. The Si-O bond and long alkyl chain in the coupling agent can make the surface of the alloy powder and the binder contact more closely, thereby improving the strength and heat resistance of the magnet. At the same time, it can also improve the magnetic permeability of the magnet to a certain extent. Therefore, the absence of a coupling agent in this example affected the inductance value, strength, and high-temperature resistance performance.

[0128] In Example 11, compared with Example 1, in the selection of the thermoplastic resin in the binder, only the first thermoplastic resin, i.e., polyamide resin, was used, which made the rigidity of the magnetic sheet relatively large, and the tightness of the combination of the base magnetic sheet, the intermediate magnetic sheet, and the covering magnetic sheet was relatively low, thus affecting the inductance value, strength, and temperature resistance performance of the finished inductor.

[0129] In Examples 13 - 14, compared with Example 1, if the mass ratio of polyamide resin and polyurethane resin in the thermoplastic resin is too high, the rigidity of the magnetic sheet will be large, and the bonding effect between the magnetic sheets during the hot pressing process will be poor, resulting in a certain degree of deterioration in the inductance value, strength, and high-temperature resistance performance of the inductor; if the mass ratio of polyamide resin and polyurethane resin in the thermoplastic resin is too low, the proportion of co-curing or forming a partial interpenetrating network structure between the first thermoplastic resin and phenolic resin in the magnet will decrease, causing the strength of the inductor magnet to decrease.

[0130] In Comparative Example 1, compared with Example 1, since the particle size of the third alloy is relatively small, it can effectively fill the gaps between the first alloy and the second alloy, increasing its packing density. As a result, the inductor magnet after curing and molding has the characteristic of high strength. Therefore, when the third alloy is not used in the selection of the soft magnetic alloy powder in Comparative Example 1, both its inductance value and strength deteriorate.

[0131] In Comparative Example 2, compared with Example 1, only thermoplastic resin was used in the selection of the binder. The thermoplastic resin has a linear and flexible chain structure, lacking the large number of three-dimensional cross-linked network structures brought by the thermosetting resin. Therefore, the strength and heat resistance of its inductor are greatly affected.

[0132] The above are only specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention fall within the protection scope and the disclosure scope of the present invention.

Claims

1. A magnetic paste, characterized in that, The magnetic slurry includes soft magnetic alloy powder, binder, and additives; The soft magnetic alloy powder includes a first alloy, a second alloy, and a third alloy; The binder includes a mixture of a thermosetting resin and a thermoplastic resin; The additives include a solvent.

2. The magnetic slurry according to claim 1, wherein Based on the total mass of the soft magnetic alloy powder being 100%, the mass fraction of the first alloy is 15 - 25%; Preferably, based on the total mass of the soft magnetic alloy powder being 100%, the mass fraction of the second alloy is 20 - 40%; Preferably, based on the total mass of the soft magnetic alloy powder being 100%, the mass fraction of the third alloy is 35 - 65%.

3. The magnetic paste according to claim 1 or 2, characterized in that, The average Wardell sphericity of the first alloy is 70 - 100%, preferably 80 - 100%; Preferably, the particle size D50 of the first alloy is 30 - 50 μm, preferably 35 - 45 μm; Preferably, the first alloy includes FeNi alloy and / or FeNiMo alloy, preferably FeNi alloy; Preferably, the average Wardell sphericity of the second alloy is 85 - 100%, preferably 90 - 100%; Preferably, the particle size D50 of the second alloy is 25 - 45 μm, preferably 30 - 40 μm; Preferably, the second alloy includes any one or a combination of at least two of FeSi alloy, FeSiAl alloy, or FeSiCr alloy, preferably FeSi alloy; Preferably, the average Wardell sphericity of the third alloy is 85 - 100%, preferably 90 - 100%; Preferably, the particle size D50 of the third alloy is 5 - 12 μm, preferably 7 - 10 μm; Preferably, the third alloy includes carbonyl iron powder and / or reduced iron powder, preferably carbonyl iron powder.

4. The magnetic paste according to any one of claims 1 to 3, characterized in that, The thermosetting resin includes boron - modified phenolic resin and / or molybdenum - modified phenolic resin; the number - average molecular weight of the thermosetting resin is 1000 - 5000; Preferably, the thermoplastic resin includes a first thermoplastic resin and / or a second thermoplastic resin; Preferably, the first thermoplastic resin includes polyamide resin and / or polysulfone resin; the number - average molecular weight of the first thermoplastic resin is 100000 - 250000; Preferably, the second thermoplastic resin includes polyurethane resin; the number - average molecular weight of the second thermoplastic resin is 50000 - 150000; Preferably, the mass ratio of the thermosetting resin to the thermoplastic resin is (2 - 4):1; Preferably, the mass ratio of the first thermoplastic resin to the second thermoplastic resin is (1 - 3):

1.

5. The magnetic slurry according to any one of claims 1-4, characterized in that The solvent includes a combination of at least two of acetone, methyl ethyl ketone, ethanol, propanol, ethyl acetate, or butyl acetate; Preferably, the additives further include a dispersant and a coupling agent; Preferably, the dispersant includes any one or a combination of at least two of BYK - 185, AKM - 0531, or SRE - 42413, preferably AKM - 0531; Preferably, the coupling agent includes a mixture of a silane coupling agent and a titanate coupling agent; the mass ratio of the silane coupling agent to the titanate coupling agent is 5:(1 - 3).

6. The magnetic slurry according to any one of claims 1-5, characterized in that The magnetic slurry comprises the following components in parts by weight:

7. A method for preparing the magnetic slurry according to any one of claims 1-6, characterized in that, The preparation method comprises: (1) mixing the first alloy, the second alloy and the third alloy to obtain soft magnetic alloy powder; (2) The soft magnetic alloy powder and a solvent are mixed to obtain the magnetic slurry.

8. The preparation method according to claim 7, characterized in that, The preparation method specifically comprises the following steps: (I) mixing the first alloy, the second alloy and the third alloy to obtain a soft magnetic alloy powder; (II) mixing the dispersant with part of the solvent, then adding the soft magnetic alloy powder, ball milling at a speed of 200-300 rpm for 4-6 hours, and drying to obtain a mixed alloy powder with a dispersant surface treatment; (III) mixing a coupling agent and a portion of a solvent, then adding the mixed alloy powder surface-treated with the dispersant to mix, and drying to obtain the mixed alloy powder surface-treated with the coupling agent; (IV) ball milling the mixed alloy powder treated with the coupling agent, the binder and the remaining solvent at a rotation speed of 150-300 rpm for 18-24 hours, and then sieving through 50-100 mesh and degassing by vacuum stirring for 10-15 minutes to obtain the magnetic slurry.

9. A magnetic sheet, characterized in that, The magnetic sheet is obtained by casting the magnetic slurry according to any one of claims 1 to 6.

10. An inductor, characterized in that, The inductor includes the magnetic sheet according to claim 9.

Citation Information

Patent Citations

  • Method for manufacturing slurry-casting type inductive element

    CN101494110A

  • NFC magnetic sheet, paste for NFC magnetic sheet, and preparation method of paste for NFC magnetic sheet

    CN103426585A

  • Magnetic slurry, preparingmethod of magnetic slurry and preparing method of magnetic sheet

    CN106887290A

  • Preparation method of magnetic slurry, common mode inductor and common mode inductor cover plate

    CN113948262A